2018
DOI: 10.1111/meca.12220
|View full text |Cite
|
Sign up to set email alerts
|

On dynamics in a Keynesian model of monetary and fiscal stabilization policy mix with twin debt accumulation

Abstract: In this paper, a six‐dimensional model of flexible prices with the monetary and fiscal policy mix, describing the development of the firms’ private debt, the output, the expected rate of inflation, the rate of interest, government expenditure, and government bonds are analyzed. The stress put on the “twin debt accumulation” means that in our model both private debt accumulation and the public debt (government bond) accumulation are explicitly introduced. Questions concerning the existence of limit cycles aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Ninomiya and Tokuda (2017) contended that their investigation may support this argument. 3 See, for example, Keen (1995), Asada (2001Asada ( , 2006, Ninomiya (2006), Hein (2007), Charles (2008a), Sasaki and Fujita (2014), Ninomiya (2018), and Asada et al (2019). 4 Nishi (2012a) investigated the dynamic relationships among income distribution, debt ratio, and capital accumulation in the Japanese economy.…”
mentioning
confidence: 99%
“…Ninomiya and Tokuda (2017) contended that their investigation may support this argument. 3 See, for example, Keen (1995), Asada (2001Asada ( , 2006, Ninomiya (2006), Hein (2007), Charles (2008a), Sasaki and Fujita (2014), Ninomiya (2018), and Asada et al (2019). 4 Nishi (2012a) investigated the dynamic relationships among income distribution, debt ratio, and capital accumulation in the Japanese economy.…”
mentioning
confidence: 99%
“…1 Taking this approach, a number of studies have demonstrated the presence of business cycles. 2 As is well known, limit cycles can be stable or unstable; stable limit cycles have inner and outer attracting domains, while unstable limit cycles have inner and outer repelling domains. In the theory of economic dynamics, both of them have important implications; it is indicated by the former that the state of an economy converges to persistent business cycles while by the latter that a stable region associated with "corridor stability" may exist.…”
mentioning
confidence: 99%
“…4 For recent exceptional investigations of the stability of periodic orbits in high-dimensional dynamic models (with dimensionality of three or more) in economics, see Asada et al [1,2] and Murakami and Zimka [30]. 5 Murakami [21] established the existence of stable limit cycles in the two-dimensional model but not in the three-or four-dimensional model.…”
mentioning
confidence: 99%
“…Typical examples of such 'Keynesian' macrodynamic models are Kaldor [23], Kalecki [24] and Goodwin [20]. Later examples of models in this tradition include Torre [47], Semmler [45], Dohtani, Misawa, Inaba, Yokoo and Owase [16], Asada, Chiarella, Flaschel and Franke [4], and Asada, Demetrian and Zimka [5], [6].…”
mentioning
confidence: 99%
“…For detailed examples of how Liu's criterion can be satisfied in a high-dimensional nonlinear dynamical system, see Maličký and Zimka[32],[33], or Asada et al[5],[6].…”
mentioning
confidence: 99%